Combining learning motivation and problem based learning using articulate storyline media for students with disabilities - Mawardi Nurullah; Cucu Atikah; Aceng Hasani (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aims to improve learning motivation and learning outcomes of students with disabilities in a Citizenship Education course through the implementation of a Problem-Based Learning (PBL) model supported by Articulate Storyline media. The research employed Classroom Action Research conducted in two cycles involving 12 students with disabilities at Pamulang University. Data were collected using a learning motivation questionnaire and cognitive achievement tests administered in the pre-cycle, cycle I, and cycle II. The results indicate an improvement in learning motivation from 33% in cycle I to 78% in cycle II. In addition, classical learning completeness increased from 33% to 83%, indicating better cognitive achievement after the implementation of the intervention. The findings suggest that the integration of PBL and interactive digital media facilitates active participation, enhances motivation, and supports inclusive learning. Therefore, the use of Articulate Storyline within a PBL framework can be an effective instructional strategy to improve motivation and learning outcomes for students with disabilities in higher education.